FAKTOR RISIKO CEDERA LUTUT BERULANG PASCA ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION - Luh Putu Surya Sintia Dewi; I Putu Gde Surya Adhitya; Anak Agung Gede Eka Septian Utama; Anak Agung Gede Angga Puspa Negara (IKesT Muhammadiyah Palembang, 2024)
Background: ACLR is an operative procedure to restore knee stability and reduce the risk of subsequent knee injury so that patients can return to sports and daily activities. Although this procedure has been successful in restoring knee stability, it is inevitable that some patients will experience the risk of postoperative subsequent knee injury. Currently, there is limited information regarding the causes of subsequent knee injury after surgery, including graft type, time of surgery, BMI, gender, age, and concomitant injuries. Therefore, the aim of this study was to identify the risk factors associated with subsequent knee injury after ACLR. Methods: This study used a prospective cohort design consisting of patients who underwent ACL reconstruction in the ACL Indonesia Community (n=116). Inclusion criteria included participants who joined the Indonesian ACL Community WhatsApp group, aged between 17 and 60 years, experienced unilateral or bilateral ACLR, and were willing to participate in this study. Exclusion criteria included the presence of fractures, infections, incomplete questionnaire, or MRI forms. In this study, secondary data were obtained through an online survey either by selecting available options or typing in additional information according to the patient's condition. It was then validated through a telephone interview to confirm the veracity of the patient's subsequent knee injury and the timing of its occurrence. Follow-up was conducted over a two-year period after the ACLR procedure to monitor the occurrence of subsequent knee injury. Results: The results of univariate and multivariate analysis using the Cox Proportional Hazard model showed that several patient characteristic variables had a significant association with the risk of subsequent knee injury after ACL reconstruction (ACLR). Some variables showed an increased risk of 1.98-3.86 times, while one variable showed a decreased risk of 0.96 times compared to the reference group. Multivariate analysis also found that individuals who sustained ACL injuries along with injuries to the meniscus and other ligaments had a risk of subsequent knee injury 3.73 times higher than those with ACL injuries alone. Conclusion: Individuals who sustained ACL injuries in addition to injuries to the meniscus and other ligaments had a higher propensity to reinjure their knee after undergoing ACL reconstruction surgery compared to individuals who only sustained ACL injuries with meniscus involvement alone.